1993
DOI: 10.1021/bi00085a023
|View full text |Cite
|
Sign up to set email alerts
|

Actin-binding peptide from smooth muscle myosin light chain kinase

Abstract: The objective of this study was to localize the actin-binding site in the smooth muscle myosin light chain kinase. Limited proteolysis by thermolysin indicated that hydrolysis of the kinase at the N-terminal end of the molecule resulted in loss of actin-binding ability. Various methods of cleavage were investigated for the generation of a discrete actin-binding peptide. The method chosen was cleavage at the cysteine residues by the 5,5'-dithiobis(2-nitrobenzoic acid)-cyanide complex. This procedure yielded an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
1

Year Published

1995
1995
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 39 publications
2
30
0
1
Order By: Relevance
“…In the presence of 1 mM EGTA, the NTCB fragment showed actin binding activity, confirming the results of Kanoh et al (14). Scatchard plots of the data showed that the NTCB fragment bound to actin filaments maximally at 0.2 mol/mol actin with a single K a of 4.8 ϫ 10…”
supporting
confidence: 88%
See 3 more Smart Citations
“…In the presence of 1 mM EGTA, the NTCB fragment showed actin binding activity, confirming the results of Kanoh et al (14). Scatchard plots of the data showed that the NTCB fragment bound to actin filaments maximally at 0.2 mol/mol actin with a single K a of 4.8 ϫ 10…”
supporting
confidence: 88%
“…The fragment consisted of the Met 1 -Lys 114 sequence (14,18) and is referred to as the NTCB fragment. Skeletal muscle actin was purified from an acetone powder of chicken breast muscle (19) and used as actin filaments after polymerization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, MLCK binds to actin thin filaments whereas its substrate, myosin, is in thick filaments (14,15). The actinbinding properties of the short MLCK are precisely identified with three repeated motifs of DFRXXL residues at the N terminus (1,16).…”
Section: Mlckmentioning
confidence: 99%